2012
DOI: 10.1103/physreva.85.052717
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron scattering by tetrahydrofuran

Abstract: Cross sections for elastic scattering of low-energy electrons by tetrahydrofuran, a prototype for the furanose ring found in the backbone of DNA, have been measured and calculated over a wide energy range, with an emphasis on energies below 6 eV, where previous data are scarce. The measurements employ a thin-aperture version of the relative-flow method, while the calculations employ the Schwinger multichannel method with an extensive treatment of polarization effects. Comparisons with earlier results, both exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 46 publications
7
47
0
Order By: Relevance
“…[24][25][26][27][28][29][33][34][35] Given that the level of accord between the various electron DCS is, in general, very good at each energy, for the sake of clarity we only show in Figure 5 the experimental results from Allan 26 and the theoretical results of Gauf et al 29 First, we observe in Figure 5 that the existing electron-impact elastic DCS are strongly forward peaked, similar to the present measured and computed positron-impact DCS. This suggests that the dipole interaction dominates over the static interaction in the scattering process at the lower energies.…”
Section: Elastic Differential Cross Sectionsmentioning
confidence: 74%
See 1 more Smart Citation
“…[24][25][26][27][28][29][33][34][35] Given that the level of accord between the various electron DCS is, in general, very good at each energy, for the sake of clarity we only show in Figure 5 the experimental results from Allan 26 and the theoretical results of Gauf et al 29 First, we observe in Figure 5 that the existing electron-impact elastic DCS are strongly forward peaked, similar to the present measured and computed positron-impact DCS. This suggests that the dipole interaction dominates over the static interaction in the scattering process at the lower energies.…”
Section: Elastic Differential Cross Sectionsmentioning
confidence: 74%
“…In particular, we note the total cross section (TCS) measurements of Zecca et al, 22 Możejko et al, 23 and Baek et al 24 Elastic differential cross section (DCS) measurements at selected impact energies have been carried out by Milosavljević et al, 25 Allan, 26 Colyer et al, 27 Dampc et al, 28 Gauf et al, 29 and Baek et al 24 Except for the work of Milosavljević et al, 25 these groups also reported elastic integral cross sections (ICS). To the best of our knowledge, the only electron-impact, discrete electronic-state excitation cross sections are those of Do et al, 30 while a review of all the available earlier work and a recommended database for electron-THF scattering can be found in Fuss et al 31 Among the theoretical studies on electron-THF scattering, we note the TCS calculation using the R-matrix method of Bouchiha et al 32 Computations of the elastic DCS have been reported by Możejko and Sanche 33 with the independent atom model (IAM), Trevisan et al 34 using the complex Kohn variational method, and Winstead and McKoy 35 and Gauf et al 29 both employing the Schwinger multichannel method (SMC). These authors, with the exception of Trevisan et al, 34 calculated the elastic ICS as well.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work is dedicated to the study of electron transport and reactivity in biological media, including vibrational and electronic excitation, dissociative attachment, electron trapping and reactivity in condensed THF along with the report of measurements of elastic and total scattering cross sections [14]. Electron-impact ionisation for THF has been studied experimentally by two groups [15,16] and theoretically by two groups [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, theoretical and experimental absolute differential cross sections (DCSs) for elastic electron scattering by THF have been reported by several groups. 6,[14][15][16][17][18][19][20] However, it must be taken into account that, contrary to THF, the furan molecule is not saturated and an existence of π orbitals makes it chemically distinct from THF. For example, the process of dissociative electron attachment, which is considered to be particularly important in radiation damage research since it could lead to DNA strand breaks, 1,2 is very different for these.…”
Section: Introductionmentioning
confidence: 99%